Am I Ready to Be an Independent Neuroradiologist? Objective Trends in Neuroradiology Fellows' Performance during the Fellowship Year - Masur, J.H.; Schmitt, J.E.; Lalevic, D.; Cook, T.S.; Bagley, L.J.; Mohan, S.; Nayate, A.P. (American Journal of Neuroradiology, 2021)
BACKGROUND AND PURPOSE: Aside from basic Accreditation Council for Graduate Medical Education guidelines, few metrics are in place to monitor fellows' progress. The purpose of this study was to determine objective trends in neuroradiology fellowship training on-call performance during an academic year.MATERIALS AND METHODS: We retrospectively reviewed the number of cross-sectional neuroimaging studies dictated with complete reports by neuroradiology fellows during independent call. Monthly trends in total call cases, report turnaround times, relationships between volume and report turnaround times, and words addended to preliminary reports by attending neuroradiologists were evaluated with regression models. Monthly variation in frequencies of call-discrepancy macros were assessed via χ2 tests. Changes in frequencies of specific macro use between fellowship semesters were assessed via serial 2-sample tests of proportions.RESULTS: From 2012 to 2017, for 29 fellows, monthly median report turnaround times significantly decreased during the academic year: July (first month) = 79 minutes (95% CI, 71–86 minutes) and June (12th month) = 55 minutes (95% CI, 52–60 minutes; P value = .023). Monthly report turnaround times were inversely correlated with total volumes for CT (r = –0.70, F = 9.639, P value = .011) but not MR imaging. Words addended to preliminary reports, a surrogate measurement of report clarity, slightly improved and discrepancy rates decreased during the last 6 months of fellowship. A nadir for report turnaround times, discrepancy errors, and words addended to reports was seen in December and January.CONCLUSIONS: Progress through fellowship correlates with a decline in report turnaround times and discrepancy rates for cross-sectional neuroimaging call studies and slight improvement in indirect quantitative measurement of report clarity. These metrics can be tracked throughout the academic year, and the midyear would be a logical time point for programs to assess objective progress of fellows and address any deficiencies.CSNIcross-sectional neuroimaging studiesRISradiology information systemRTATreport turnaround time